Synthesis of the homochiral metal-organic framework DUT-129 based on a chiral dicarboxylate linker with 6 stereocenters - Kutzscher, Christel; Janssen-Mueller, Daniel; Notzon, Andreas; Stoeck, Ulrich; Bon, Volodymyr; Senkovska, Irena; Kaskel, Stefan; Glorius, Frank (Crystengcomm, 2017)
A dicarboxylate linker with an exceptionally high density of stereogenic centers for the development of new chiral metal-organic frameworks (MOFs) was synthesized. A bicyclic functionality forms the backbone of the linker, creating a linear structural analogue of terephthalic acid. The linker includes two side chains bearing secondary amine functionalities, which could induce catalytic activity of the resulting MOF structures for nucleophilic organocatalysis. The new chiral linker was used to synthesize a zinc-based MOF structure, named DUT-129. Single crystal X-ray analysis identified the porous framework with a sodalite (sod) topology. The bulky side groups of the chiral linker limit the pore accessibility of DUT-129, which was proven by liquid phase adsorption experiments. The calculated pore limiting diameter of 5.2 Å indicates pore accessibility exclusive for small molecules, such as linear and branched alkanes. Therefore, the new MOF DUT-129 is expected to show high size selectivity in adsorption and separation applications in combination with high enantiomeric discrimination.
CRIS-Team Scopus Importer:2022-04-14